Overall quit in triple users of conventional cigarette, e-cigarette and heated tobacco product among healthy adults: a Korea Medical Institute health check-up study - Sun Ha Jee; Heejin Kimm; Keum Ji Jung; Hye Won Yun (BMJ Open)
Objective While multiuse patterns of e-cigarettes (EC) or heated tobacco products (HTP) with conventional cigarettes (CC) have been reported, smoking cessation of multiusers is not well known. We aimed to analyse overall quit in triple users of CC, EC and HTP among healthy adults.Methods A questionnaire was conducted on 89 360 adults who visited the Korea Medical Institute health check-ups in Seoul, Korea, from May 2018 to September 2019. Among 38 812 ever smokers, 9252 were ever triple users of CC, EC and HTP. Frequency and related factors of overall quit were analysed in the cross-sectional study.Results The average age was 38.8±9.0 years, and 8458 (91.4%) were men. There were 5329 (57.6%) current triple users, 3547 (38.3%) single or dual product quitters and 376 (4.1%) overall quitters. Among the former triple users, the most common tobacco product use pattern was ‘dual quit of EC and HTP (eg, current CC use)’ both in men (21.3%) and women (26.3%). Age 60s or older (OR 8.5, 95% CI 5.2 to 13.8), women (OR 1.7, 95% CI 1.1 to 2.5), no hyperlipidaemia and married status were significantly related to overall quit.Conclusion The most common pathway for ‘ever triple users’ of the three tobacco products was ‘current triple users’, and the second was ‘CC users’. Single or dual product quitters could continue to smoke by EC or HTP instead of quit. Further research on overall quit will be needed to develop effective regulations.